Shaking table test and numerical analysis of a coal-fired power plant equipped with large mass ratio multiple tuned mass damper (LMTMD). (November 2021) - Kang, Ying-jie; Peng, Ling-yun; Pan, Peng; Xiao, Gen-qi; Wang, Hai-shen
Abstract: In an industrial building, heavy equipment can be configured as the mass of multiple tuned mass dampers with large mass ratio (LMTMD) without the addition of extra mass. This paper systematically investigates the effects of the LMTMD for the mitigation of structural seismic responses in industrial buildings such as a coal-fired power plant. A detailed design method was proposed based on numerical modeling, optimization of the key parameters and evaluation of the seismic performance of the structure. Shaking table tests were conducted on a scaled model and time-history analysis were performed with general purpose finite element program ABAQUS. The coal-fired power plant with mass irregularity due to the installation of heavy coal buckets was selected as the sample structure. The heavy coal buckets are utilized as the mass of the LMTMD. The feasibility and effectiveness of the proposed design method were demonstrated through tests and analyses. The simulation results agree well with the test results, which validate the accuracy of the numerical analyses and suggest that the LMTMD can effectively reduce the structural dynamic response and significantly improve the seismic performance of the thermal power plant structure. The reduction rate of the maximum inter-story drift was more than 32.6% under earthquake excitations, demonstrating the effectiveness and strong robustness of the LMTMD. The failure mode of the structure was optimized by the reduced damage concentration. Highlights: A detailed design method for a structure equipped with LMTMD was proposed. The feasibility and effectiveness of the design method were demonstrated through tests and numerical analyses. Heavy coal buckets that cause the mass irregularity of the structure were utilized as the mass of the LMTMD. The LMTMD can significantly improve the seismic performance of the thermal power plant structure.